Local amplifiers of IL-4Ra-mediated macrophage activation promote repair in lung and liver - Minutti, Carlos M.; Jackson-Jones, Lucy H.; Garcia-Fojeda, Belen; Knipper, Johanna A.; Sutherland, Tara E.; Logan, Nicola; Rinqvist, Emma; Guillamat-Prats, Raquel; Ferenbach, David A.; Artigas, Antonio; Stamme, Cordula; Chroneos, Zissis C.; et al. (Science, 2017)
The type 2 immune response controls helminth infection and maintains tissue homeostasis but can lead to allergy and fibrosis if not adequately regulated.We have discovered local tissue-specific amplifiers of type 2-mediated macrophage activation. In the lung, surfactant protein A (SP-A) enhanced interleukin-4 (IL-4)-dependent macrophage proliferation and activation, accelerating parasite clearance and reducing pulmonary injury after infection with a lung-migrating helminth. In the peritoneal cavity and liver, C1q enhancement of type 2 macrophage activation was required for liver repair after bacterial infection, but resulted in fibrosis after peritoneal dialysis. IL-4 drives production of these structurally related defense collagens, SP-A and C1q, and the expression of their receptor, myosin 18A. These findings reveal the existence within different tissues of an amplification system needed for local type 2 responses.
CRIS-Team Scopus Importer:2023-03-23